Management Policy During Pandemic and Post Pandemic, Kampung Labirin Tourism Village Central Bogor - Achyarsyah, Padri; Nugraha, Rizki Nurul; Awaloedin, Dipa Teruna (Westscience Press, 2023)
The Tourism Village sector is still a mainstay in encouraging the revival of the village economy after the pandemic. The importance of holding village-based tourism activities aims to improve the socio-economic conditions of the relevant village communities. During the Pandemic, Tourism activities were temporarily stopped but the participation of all parties was needed, including the community in the local area by helping to maintain cleanliness and environmental sustainability in tourist villages. Apart from being built by Astra's CSR, Labirin Village is also collaborating with the Rain Terminal Foundation to develop the 3 hectare village into a tourist village. This research aims to analyze the management policies implemented during the COVID-19 pandemic and post-pandemic in the Kampung Labirin Tourism Village. This village is a tourist destination famous for its jungle maze, which attracted many tourists before the pandemic. However, the COVID-19 pandemic caused a significant decline in tourist visits and had a negative impact on the local economy. The results of this research show that the Kampung Labirin Tourism Village has implemented various management policies during the COVID-19 pandemic to mitigate its impacts. These policies include reducing visiting capacity, implementing strict health protocols, developing digital tourism products, and collaborating with related parties to promote safety and cleanliness.